واقع إدارة المعرفة لدى مديري المدارس الإعدادية في مركز محافظة واسط من وجهة نظر المدرسين والمدرسات - كاطع سموم م.د عبد (Journal of College of Education, 2021)
The research aims to identify the degree of knowledge management at the junior high school principals from the perspective of teachers, and to identify the differences between the responses of faculty members by gender (male - female), and to identify the differences between the responses of faculty members by years of service (5-10 ) years, and more than 10 years, either limits Search: the current research is limited to faculty members in the junior high schools in the Kut district center for the academic year 2016-2017 and the research community from all the teachers in the middle school affiliated consists to the General Directorate for Education and Waist in Kut district center totaling (694) as a teacher and a school by 355 males and 339 females, due to the heterogeneity of the research community has been stratified random sample represents withdraw (35%) of the research community overall, and thus the total sample was 200 teachers the School of prep schools, of which 100 teachers and 100 schools have been selected random manner from the research community and statistical methods: use a researcher number of statistical methods within statistical bag to seal the objectives of the research are Altaia test for two independent samples, to find differences in the two variables on according to the two variables (type - length of service), but the most important is the conclusion the researcher the following, that the junior high school administration managers to know, but not the level of ambition, and it was for managers and managers experienced teams in the application of knowledge management for the benefit of managers who have much experience, but the most important recommendations train school principals in the Directorate-General for Education and Waist knowledge management through workshops and training courses and seminars to raise awareness in Kiffa benefit from the knowledge, and the provision of modern technologies that facilitate the work of school principals and reached knowledge and take advantage of the most important proposals: (1) conduct a study to determine the degree of knowledge management among principals at other stages (elementary and middle) 2. conduct a study to determine the degree of knowledge management supervisors jurisdiction in junior high school.